Effects of red orange juice intake on endothelial function and inflammatory markers in adult subjects with increased cardiovascular risk - Buscemi, Silvio; Rosafio, Giuseppe; Arcoleo, Gioacchina; Mattina, Alessandro; Canino, Baldassare; Montana, Maria; Verga, Salvatore; Rini, Giovanbattista (The American journal of clinical nutrition, 2012)
Oxidative and inflammatory stresses are involved in the pathogenesis of atherosclerosis. The consumption of fruit and vegetables is associated with improved health and reduced cardiovascular risk. Red oranges have a high content of antioxidant and antiinflammatory substances, but there is a paucity of data concerning their effects on cardiovascular biomarkers in subjects with increased cardiovascular risk. We investigated the effect of red orange juice intake on endothelial function, oxidative stress, and markers of inflammation in subjects with increased cardiovascular risk. Nineteen nondiabetic subjects with increased cardiovascular risk (aged 27-56 y) were included in a randomized, placebo-controlled, single-blind crossover study and compared with 12 healthy, nonobese control subjects. In 2 periods of 7 d each with a 3-d interval, each participant alternatively received 500 mL red orange juice/d and 500 mL placebo/d in a random sequence. All measurements were performed in the morning after overnight fasting. Endothelial function, which was measured as flow-mediated dilation, significantly improved and was normalized (5.7% compared with 7.9%; P < 0.005) after 1 wk of red orange juice consumption. Similarly, concentrations of high-sensitivity C-reactive protein, IL-6, and TNF-α significantly decreased (P < 0.001). Red orange juice had no significant effect on nitric oxide plasma concentrations. A 7-d consumption of red orange juice ameliorates endothelial function and reduces inflammation in nondiabetic subjects with increased cardiovascular risk. This trial was registered at biomedcentral.com as ISRCTN39987296.